Supramolecular silk from a peptide hydrogel. (7th December 2016) - Zhan, Jie; Cai, Yanbin; Ji, Shenglu; Shang, Yuna; Gao, Jie; Yang, Zhimou
Abstract : A macroscopic silk-like fiber consisting of aligned nanotubes from a self-assembled peptide hydrogel is generated using a simple and fast method. Abstract : A macroscopic silk-like fiber can be drawn directly from a hydrogel self-assembled from peptides, which offers an easy and versatile method for generating materials with hierarchically ordered structures over different scales and extends the utility of peptide hydrogels.